Eosinophils Protect Mice From Angiotensin-II Perfusion–Induced Abdominal Aortic Aneurysm. Issue 2 (22nd January 2021) - Liu, Cong-Lin; Liu, Xin; Zhang, Yuanyuan; Liu, Jing; Yang, Chongzhe; Luo, Songyuan; Liu, Tianxiao; Wang, Yunzhe; Lindholt, Jes S.; Diederichsen, Axel; Rasmussen, Lars M.; Dahl, Marie; et al.
Abstract : Rationale: Blood eosinophil count and ECP (eosinophil cationic protein) associate with human cardiovascular diseases. Yet, whether eosinophils play a role in cardiovascular disease remains untested. The current study detected eosinophil accumulation in human and murine abdominal aortic aneurysm (AAA) lesions, suggesting eosinophil participation in this aortic disease. Objective: To test whether and how eosinophils affect AAA growth. Methods and Results: Population-based randomized clinically controlled screening trials revealed higher blood eosinophil count in 579 male patients with AAA than in 5063 non-AAA control (0.236±0.182 versus 0.211±0.154, 10 9 /L, P <0.001). Univariate (odds ratio, 1.381, P <0.001) and multivariate (odds ratio, 1.237, P =0.031) logistic regression analyses indicated that increased blood eosinophil count in patients with AAA served as an independent risk factor of human AAA. Immunostaining and immunoblot analyses detected eosinophil accumulation and eosinophil cationic protein expression in human and murine AAA lesions. Results showed that eosinophil deficiency exacerbated AAA growth with increased lesion inflammatory cell contents, matrix-degrading protease activity, angiogenesis, cell proliferation and apoptosis, and smooth muscle cell loss using angiotensin-II perfusion–induced AAA in Apoe −/− and eosinophil-deficient Apoe −/− ΔdblGATA mice. Eosinophil deficiency increased lesion chemokine expression, muted lesion expression of IL (interleukin) 4 and eosinophil-associated-ribonuclease-1 (mEar1 [mouse EOS-associated-ribonuclease-1], human ECP homolog), and slanted M1 macrophage polarization. In cultured macrophages and monocytes, eosinophil-derived IL4 and mEar1 polarized M2 macrophages, suppressed CD11b + Ly6C hi monocytes, and increased CD11b + Ly6C lo monocytes. mEar1 treatment or adoptive transfer of eosinophil from wild-type and Il13 −/− mice, but not eosinophil from Il4 −/− mice, blocked AAA growth in Apoe −/− ΔdblGATA mice. Immunofluorescent staining and immunoblot analyses demonstrated a role for eosinophil IL4 and mEar1 in blocking NF-κB (nuclear factor-κB) activation in macrophages, smooth muscle cells, and endothelial cells. Conclusions: Eosinophils play a protective role in AAA by releasing IL4 and cationic proteins such as mEar1 to regulate macrophage and monocyte polarization and to block NF-κB activation in aortic inflammatory and vascular cells. Abstract : Supplemental Digital Content is available in the text.